The Presidents in American history - Beard, Charles Austin 1874-1948 (J. Messner, 1953)
Briefly summarizes the achievements of each presidential administration from Washington to Nixon. Includes a biographical digest giving basic facts about each President, a list of Vice-Presidents and cabinet members, and the results of each presidential election.